Transformasi Wisata Kapalo Banda: Studi Strategis Dengan Matriks EFI, EFE, IE, SWOT, Dan QSPM - Alfikri; Silfia; Darnetti; Iryani, Nelvia (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: This research aims to design an appropriate strategy that can be applied to efforts to develop the Kapalo Banda tourist attraction. Methode: Qualitative Descriptive, namely this research describes the condition of objects, both external and internal, naturally and objectively using the strategy selection stage in the form of the input stage with the EFI Matrix and EFE Matrix, the matching stage with the IE Matrix and SWOT Matrix, and the decision stage with the QSPM Matrix Research Finding: The results of data analysis at the matching stage using the IE Matrix obtained a strategy in Quadrant II. Then, at the strategy matching stage with the SWOT Matrix, eight types of strategies were obtained that could be used in the development of Kapalo Banda tourism. Theoretical contribution: This study can explain the importance of tourism area development strategies for attracting visitors by continuously identifying internal strengths and external threats. Practical implication: The resulting alternative strategies can be implemented in stages, based on the needs and capabilities of existing resources. Research limitation: This research focuses on the Kapalo Banda tourist attraction in Kenagarian Taram, Limapuluh Kota Regency